Keadilan Prosedural dalam Partisipasi Penganggaran dan Aspek Peningkatan Komitmen Afektif: Studi Kasus pada PT X Indonesia - Kurniawan, Mas Ariandi (Jurnal KIAFE, 2019)
AbstractProcedural justice has been a part of management system to control behavior of human resources. Motstly, the current study explored the impact of procedural justice in enhancing budgetary participation and affective commitment in the corporate. The objectives of this research are: 1) to identify the procedural justice of managers; 2) to identify the partcipation of managers on budgetary process; 3) to analyze the procedural justice in increasing budgetary participation of managers; and 4) to analyze the procedural justice as the raising aspect of affective commitment.The research was conducted based on the data investigated from 10 managers as the object who directly involved to budgetary process and decision making, in PT X Indonesia East Jakarta. In term of qualitative approachment, this research applied Spradley Analysis Model (James Spradley, 1980) to observe domains, collect datas through in-depth interview, and analyze informations to emphasize the result.The empirical result of this research revealed the procedural justice has been properly implemented in every single procedure and decision in the corporate. It was also found that the managers were completely involved in the budgetary process based on their role and fuction. Eventually, the analysis found that a sensibly implementation of procedural justice can strengthen budgetary participation and affective commitment. Keywords: procedural justice, budgetary participation, affective commitmentREFERENCESAlannita. Ni Putu dan I Gusti Nngurah Agung Suaryana. 2014. "Pengaruh Kecanggihan Teknologi Informasi, Partisipasi Manajemen, dan Kemampuan Teknik Pemakai Sistem Informasi Akuntansi Pada Kinerja Individu". E-Jurnal Akuntansi Universitas Udayana, Vol. 6 No.2, Hal. 33-45.Arifin Zaenal. 2017. "Pengaruh Insenttif Terhadap Kinerja Karyawan". E-Journal Administrasi Bisnis. Vol. 5 No. 4, Hal. 1292-1303.Baridwan, Zaki. 2001. Sistem Penyususnan dan Prosedur. Edisi Kelima. UGM Yogyakarta: BPFE.Dewi, Ni Made Utari Sintia dan I Made Sadha Suardikha. 2015. "Pengaruh Kemampuan Teknik Pemakai SIA, Partisipasi Manajemen, Insentif, Faktor Demografi pada Kinerja Individu". E-Jurnal Akuntansi Universitas Udayana, Vol. 13 No. 2, Hal.446-460.Handoko T. Hani. 2002. Manajemen Personalia dan Sumber Daya Manusia. Edisi II. Cetakan Keempat Belas. Yogyakarta: Penerbit BPEE. Ivancevich, Jonh M, Robert Konopaske, and Michael T. Matteson. 2006. Organizational Behavior and Management. 7th Edition. Erlangga.Juju, D. dan Sulianta, F. 2010. Branding Promotion with Social Networks. Jakarta: PT Elex Media Komputindo.Komala, Adeh Ratna. 2012. "The Influence of The Accounting Manager Knowledge and The Top Management Support to the Accounting Information System and It"™s Impact on the Quality of Accounting Information". Survey In Management Institution of Zakat In Bandung. 3rd International Conference on Business and Economic Research (3rd Icber 2012) Procceding.Kouser, Rehana, Gul e Rana et. Al. 2011. "Determinant of AIS Effectiveness: Assesment Thereof in Pakistan". International Journal of Contemporar Business Studies. Vol. 2 No. 12, Page. 6-12.Krismiaji. 2002. Sistem Informasi Akuntansi. Yogyakarta: AMP YKPN.